Examining the effect of nearby armed conflict on access to maternal and child health services in Burkina Faso’s primary healthcare facilities - Amberg, Felix; Blanchet, Karl; Singh, Neha S.; Ridde, Valéry; Bonnet, Emmanuel; Yaméogo, Pierre; Sie, Ali; Seynou, Mariam; Lohmann, Julia; De Allegri, Manuela (BMJ global health, 2025)
Background Armed conflict is increasing in sub-Saharan Africa, impacting access to vital health services. However, scant evidence exists on the effects of the recently escalated conflict in Burkina Faso, a country severely affected by rising violence.Methods We conducted a longitudinal study, aligning conflict event data from the Uppsala Conflict Data Program with Burkina Faso’s Health Management Information System data spanning from 2013 to 2021. Applying negative binomial regression models with health facility fixed effects, we assessed the impact of nearby armed conflict events (within 25 km of primary healthcare centres) on access to six essential maternal and child health services. We investigated effect heterogeneity by varying conflict intensity and duration, and facility characteristics.Results Any nearby armed conflict significantly reduced the incidence of all examined health services, except for non-significant caesarean section declines. Specifically, antenatal care 4 visits decreased by 3.9%, facility-based deliveries by 7.2%, caesarean sections by 9.4%, postnatal care 1 visits by 4.3% and outpatient care visits for children under 5 and aged 5-14 by 7.2% and 12.0%, respectively. High-intensity conflict events significantly amplified the negative effects across all health services. We observed less pronounced effects on children under 5 compared with those aged 5-14 not encompassed by existing fee removal policies. Prolonged conflicts did not adversely affect outpatient care visits for children. Rural facilities bore a more pronounced effect than urban facilities.Conclusions Our findings show a significant disruption of health services due to contemporaneous conflict in Burkina Faso. However, child curative care services seem to exhibit a stabilisation trend in prolonged conflicts, and the mitigating effects of existing fee removal policies were evident. This underscores the need for nuanced policy interventions that consider varying conflict intensities, service types and financing schemes and highlights the importance of detailed, fine-scale analyses during conflict scenarios.
Zuerst veröffentlicht: 19. Juni 2025
Gesehen am 24.10.2025